Immunomodulatory and Antioxidant Drugs in Glaucoma Treatment - Francesco Buonfiglio; Norbert Pfeiffer; Adrian Gericke (MDPI AG, 2023)
Glaucoma, a group of diseases characterized by progressive retinal ganglion cell loss, cupping of the optic disc, and a typical pattern of visual field defects, is a leading cause of severe visual impairment and blindness worldwide. Elevated intraocular pressure (IOP) is the leading risk factor for glaucoma development. However, glaucoma can also develop at normal pressure levels. An increased susceptibility of retinal ganglion cells to IOP, systemic vascular dysregulation, endothelial dysfunction, and autoimmune imbalances have been suggested as playing a role in the pathophysiology of normal-tension glaucoma. Since inflammation and oxidative stress play a role in all forms of glaucoma, the goal of this review article is to present an overview of the inflammatory and pro-oxidant mechanisms in the pathophysiology of glaucoma and to discuss immunomodulatory and antioxidant treatment approaches.